Mediating effect of utilisation in the relation between loan services from PSBs and capital formation of MSMEs: A study of Purba and Paschim Medinipur districts of West Bengal - Sajijul Islam; Debdas Ganguly (Journal of Global Entrepreneurship Research, 2019)
The micro, small, and medium enterprises (MSMEs) have been acknowledged as the engine of economic growth and for promoting equitable progress all over the world. Let there be any category of countries, the existence of MSMEs is predictable. The MSME sector is playing a pivotal role majorly in employment generation at low capital cost.
Keywords: G21; G24; H81; L26; L31; L32; 650; Public sector banks; Utility of loan service; Utilisation of fund; Capital formation; MSMEs